Environmental conditions at the Last Interglacial (Eemian) site Neumark‐Nord 2, Germany inferred from stable isotope analysis of freshwater mollusc opercula. (1st June 2020) - Milano, Stefania; Pop, Eduard; Kuijper, Wim; Roebroeks, Wil; Gaudzinski‐Windheuser, Sabine; Penkman, Kirsty; Kindler, Lutz; Britton, Kate
Abstract : Mollusc biogenic carbonates are valuable records of past environmental conditions. In particular, carbonate oxygen (δ 18 O) and carbon (δ 13 C) stable isotopes can be used to reconstruct different physical and chemical parameters, according to the different genera used (marine, freshwater or terrestrial). The Last Interglacial (early Eemian) palaeolake of Neumark‐Nord 2 (NN2), Germany provides an excellent example of a Neanderthal archaeological site with abundant freshwater carbonate remains. As in other European contexts, one of the most abundant species is Bithynia tentaculata . In order to provide a robust regional baseline for the interpretation of the archaeological data, this study includes a calibration phase on modern B. tentaculata opercula. The results indicate that these calcitic structures are likely to be subjected to a growth slowdown/cessation during summer, which influences their geochemistry, reflecting mainly the water properties of the rest of the year. This modern calibration, together with the existing palaeoenvironmental reconstructions developed for NN2 (e.g. pollen data), represents a valuable opportunity to establish B. tentaculata opercula as reliable environmental proxies applicable to several other freshwater contexts. The isotope data of the NN2 opercula, in agreement with the pollen record, indicate that the major archaeological horizon was formed during a rather wet period and potentially in a semi‐forested environment. However, human occupation occurred also during drier phases at the site and within a wide temperature range, indicating the absence of restricted environmental preferences by the local Neanderthal groups.